A specific time course for mobilization of peripheral blood CD34+ cells after plerixafor injection in very poor mobilizer patients: impact on the timing of the apheresis procedure. Issue 3 (21st June 2012) - Lefrère, François; Mauge, Laeticia; Réa, Delphine; Ribeil, Jean‐Antoine; Dal Cortivo, Liliane; Brignier, Anne C.; Aoun, Charbel; Larghéro, Jérôme; Cavazzana‐Calvo, Marina; Micléa, Jean‐Michel
<x xml:space="preserve">Abstract</x> BACKGROUND: This report describes the specific kinetics of the peripheral blood (PB) CD34+ cell concentration in a selected group of very poor stem cell mobilizer patients treated with granulocyte–colony‐stimulating factor (G‐CSF) and plerixafor and determines the kinetics' impact on apheresis. STUDY DESIGN AND METHODS: All patients had previously experienced at least two failures of mobilization (without use of plerixafor). The present salvage therapy consisted in the administration of 10 µg/kg/day G‐CSF for 5 days added to a dose of plerixafor administered at between 5 a.m. and 6 a.m. on Day 5. The PB CD34+ cell counts were tested every 3 hours thereafter. Apheresis was initiated as soon as the PB CD34+ cell count reached 10 × 106/L. RESULTS: A PB CD34+ cell count higher than 10 × 106/L was observed as soon as 3 hours after plerixafor administration in 10 of the 11 patients who reached this threshold at some point in the monitoring process. Interestingly, all patients presented an early decrease in the PB CD34+ cell count 8 to 12 hours after plerixafor administration (below 10 × 106/L for seven patients). CONCLUSION: Had such patients been tested for PB CD34+ cell mobilization according to conventional criteria (i.e., 11 hr after plerixafor administration), apheresis would not have been performed at the optimal timing. For very poor stem cell mobilizer patients, early monitoring of PB CD34+ cell count may be required for the optimal initiation of apheresis.